SUBCONSCIOUS GASLIGHTING: COVERT ADMINISTRATION OF CONTROL OVER WOMEN IN A MIDSUMMER NIGHT’S DREAM - Kaushik, Shalini; Dubey, Yogesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Gaslighting, as a verb, is defined as a type of conscious manipulation that hits the gaslightee at the emotional and psychological levels. The concept of gaslighting seems to have evolved from the play Gas Light (1938), which was later adapted into a film, Gaslight, in 1944. Gaslighting is considered a colloquial term, but its implications are grave. While comedies were intended for the masses, the psychological manipulation inflicted upon the recipient cannot be dismissed as mere entertainment. Evidently, the term "gaslight" in its current usage did not exist before 1938; however, the concept has long been present in society. The male characters, namely Theseus and Oberon in A Midsummer Night's Dream, do not consciously manipulate the women but inadvertently gaslight them, as the men are unaware of their actions' impact on the women. The subordination of the female sex has historically been presented as normative. There is a redefining of the idea of gaslighting by adding the element of the subconscious to it, contrary to conscious manipulation, which implies gaslighting proper. This subconscious gaslighting could point towards the disguised administration of control that men in the play have over women, namely Hippolyta, Titania, Hermia, and Helena, thus infiltrating the psyche of women, defiling their sisterhood, and normalizing the patriarchal notions.